Derivative Actions As Legal Protection For Minority Investors In Public Companies In Indonesia - Zulfikri Akramul Akbar; Arlansyah Harahap; Duhita Driyah Suprapti; Sang Ayu Putu Rahayu (Journal of Human Interaction and Social Studies, 2026)
This study examines the effectiveness of derivative actions as a legal protection mechanism for minority investors in Indonesian public companies. The research is motivated by the growing participation of retail investors in the capital market and the persistent limitations affecting shareholder access to derivative litigation under Indonesian company law. Employing a non empirical normative legal research design, the study analyzes statutory provisions, legal doctrines, and theoretical perspectives through statute and conceptual approaches. Primary legal materials consist of Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 8 of 1995 concerning Capital Market, and Law Number 4 of 2023 concerning Financial Sector Development and Strengthening, complemented by scholarly literature and comparative legal sources. The findings demonstrate that the ten percent ownership threshold creates a structural incompatibility when applied to public companies characterized by dispersed share ownership and significant coordination barriers. The threshold transforms derivative actions into a procedurally inaccessible remedy for minority investors and weakens substantive access to justice. The study proposes a reconstructed framework based on threshold differentiation, leave of court mechanisms, regulatory derivative actions, and strengthened institutional involvement of the Financial Services Authority to achieve a more inclusive and effective system of investor protection.